2000
DOI: 10.1051/agro:2000147
|View full text |Cite
|
Sign up to set email alerts
|

Influence of humic acid on sorption of Co(II), Sr(II), and Se(IV) on goethite

Abstract: -This work examined the influence of a leonardite humic acid on the sorption of Co(II), Sr(II), and Se(IV) onto goethite as a function of pH. The sorption of humic acid and ions alone was first studied. The humic acid sorbs appreciably to the goethite surface according to a reversible process, with a maximum sorption of 19 mg of total organic carbon per g of goethite reached at lower pH values (≈ 5). Cobalt and selenium are significantly sorbed on goethite while strontium is only weakly sorbed. In the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 14 publications
1
13
1
Order By: Relevance
“…OM favors indeed adsorption and many works are in accordance with this conclusion. So, for Masset et al (2000), humic substances enhance the sorption of positive ions by making the surface more negative.…”
Section: Organic Matter Effectmentioning
confidence: 99%
“…OM favors indeed adsorption and many works are in accordance with this conclusion. So, for Masset et al (2000), humic substances enhance the sorption of positive ions by making the surface more negative.…”
Section: Organic Matter Effectmentioning
confidence: 99%
“…The adsorption of organic matter on the solid surfaces (oxides or clay surfaces) is due to electrostatic interactions and specific adsorption via ligand exchange (23,24). Several authors have already observed this particular effect of humic or fulvic acid on the charge and the stability of mineral colloids (25)(26)(27). For concentration values of humic acid lower than 0.2 mg/L, the suspension is slightly destabilized and the corresponding absolute value of zeta potential slightly diminishes.…”
Section: Stability and Surface Properties Of Kaolinite In Presence Ofmentioning
confidence: 99%
“…Many of the studies investigating the role of organic matter in adsorption processes on mineral surfaces (Du et al, 1999;Lenhart and Honeyman, 1999;Masset et al, 2000) have focused on metal cations, particularly those that occur as contaminants in natural environments. These types of systems are complex, because as well as the interactions of the cations and organic matter with the surface, there also exist interactions between the cations and either the dissolved organic matter or the organic matter that is adsorbed on the mineral surface.…”
Section: Introductionmentioning
confidence: 99%